Fish Health Management Considerations in Recirculating Aquaculture Systems - Part 1: Introduction and General Principles - Roy Yanong (EDIS, 2004)
Recirculating aquaculture systems, also known as water reuse systems, are commonly found in aquaculture production facilities, public aquaria, tropical fish wholesale operations, and retail pet stores. When properly managed, these systems have the advantages of both reducing overall water usage, as compared to flow-through systems, and improving control of many aspects of nutrition and water quality, as compared to pond systems. However, recirculating systems have their own unique set of problems. They are not a substitute for good management and often require more time and care than flow-through systems. They certainly are not a “silver-bullet” for eliminating fish diseases. In addition, defining the primary intended use of a system will help optimize efficiency and utility in the design process. This series of circulars – Fish Health Management Considerations in Recirculating Aquaculture Systems: Parts 1, 2 and 3 – provides basic information that should assist the beginning- or intermediate-level aquaculturist interested in working successfully with recirculating systems. This circular, Part 1, provides basic principles and guidelines for preventative medicine and system design. This document is Circular 120, one of a series of the Fisheries and Aquatic Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: December 2003.